iudad Visible versus ciudad invisible: la gestión del riesgo por inundaciones en la ciudad de Buenos Aires. - González, Silvia G. (Universidad del Rosario, 2010)
Floods are the main risk of natural origin in the city of Buenos Aires. Although they are originated by intense rainfall or level rising of the Río de la plata, the complex network of urban actions and decisions has amplied the treta and the natural hydric system has become a technological one.